2018
DOI: 10.1002/jsfa.9332
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 after application of lactic acid bacteria

Abstract: LAB surface treatments have the potential to improve the safety of leafy green plants as a preharvest food safety intervention when combined with good agricultural practices. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…LAB have also been evaluated as biocontrol at the preharvest level in fresh produce. Laury‐Shaw, Gragg, Echeverry, and Brashears (2019) demonstrated that spray application of a LAB cocktail containing Lactobacillus acidophilus , Lactobacillus crispatus , Pediococcus acidilactici, and Lactococcus lactis (9 log CFU/ml) reduced E. coli O157:H7 on spinach by 2.7 log, when the pathogen inoculum was at 5 log CFU/ml. These previous findings agree with the current study that LAB exerted antimicrobial activity against bacterial pathogens when pathogen populations were lower than those of the LAB.…”
Section: Discussionmentioning
confidence: 99%
“…LAB have also been evaluated as biocontrol at the preharvest level in fresh produce. Laury‐Shaw, Gragg, Echeverry, and Brashears (2019) demonstrated that spray application of a LAB cocktail containing Lactobacillus acidophilus , Lactobacillus crispatus , Pediococcus acidilactici, and Lactococcus lactis (9 log CFU/ml) reduced E. coli O157:H7 on spinach by 2.7 log, when the pathogen inoculum was at 5 log CFU/ml. These previous findings agree with the current study that LAB exerted antimicrobial activity against bacterial pathogens when pathogen populations were lower than those of the LAB.…”
Section: Discussionmentioning
confidence: 99%
“…lactis on spinach leaves reduces (approximately 3 log 10 CFU/g) the amount of E. coli O157:H7 viable cells, previously inoculated to the spinach leaves. Additionally, it was observed that the electrostatic spraying of LAB's tested, keeps the E. coli burden low (approximately in 1 log 10 CFU/g) on the spinach leaves, from the application of the LAB and until the harvest of spinach leaves (Laury‐Shaw et al, 2019). Also, in spinach and lettuce leaves, the spraying of a LAB cocktail ( L. lactis , Lactiplantibacillus plantarum , Lactobacillus johnsonii , and L. acidophilus ) reduced in 1–2 log 10 the viable cells of L. monocytogenes and E. coli O157:H7, under growth chamber conditions.…”
Section: Biological Control Agents For Human Pathogens On Producementioning
confidence: 99%
“…The earlier implementation of LAB to agricultural and horticultural crops may reduce the risk factors without disturbing the ecosystem. For example, Laury-Shaw et al, demonstrated that an LAB aqueous solution spray could reduce the E. coli growth in spinach [ 37 ].…”
Section: Biocontrol Agents Of Labmentioning
confidence: 99%